2012
DOI: 10.1074/jbc.m111.335547
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Acyl Protein Transferases and Thioesterases Control Surface Expression of Calcium-activated Potassium Channels

Abstract: Background: Enzymes controlling (de)palmitoylation of ion channels are poorly defined.Results: Palmitoylation of BK channels by zDHHC22 and zDHHC23 and depalmitoylation by LYPLA1 and LYPLAL1 controls BK channel cell surface expression.Conclusion: Acyl protein transferases and thioesterases display substrate specificity and control BK channel surface expression.Significance: Understanding how channels are (de)palmitoylated is essential for defining the role of palmitoylation in ion channel physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(149 citation statements)
references
References 34 publications
5
142
2
Order By: Relevance
“…However, recent reports indicate that palmitoylation also regulates protein trafficking to many distinct intracellular compartments due to its sorting role (7,9). For example, it has been reported that specific PATs and thioesterases regulate surface expression of important proteins such as calcium-activated potassium channels (27). Moreover, palmitoylation increases the affinity for membrane localization, and depalmitoylation plays a vital role in recycling and/or degradation of proteins that undergo S-palmitoylation (9, 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent reports indicate that palmitoylation also regulates protein trafficking to many distinct intracellular compartments due to its sorting role (7,9). For example, it has been reported that specific PATs and thioesterases regulate surface expression of important proteins such as calcium-activated potassium channels (27). Moreover, palmitoylation increases the affinity for membrane localization, and depalmitoylation plays a vital role in recycling and/or degradation of proteins that undergo S-palmitoylation (9, 10).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, dynamic palmitoylation of Apt1 and Apt2 promoted that of their substrates, H-Ras and GAP-43, respectively. Interestingly, it has been reported that surface expression of calcium-activated potassium channels are regulated by two of the 23 mammalian PATs (DHHC22 and DHHC23), which catalyze palmitoylation, although depalmitoylation is catalyzed only by APT1 and not by APT2 (27). We propose that both of these cytosolic thioesterases require dynamic palmitoylation for their own steadystate membrane localization, which is essential for their function in promoting dynamic palmitoylation and function of their substrates, H-Ras and GAP-43, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, APT1 activity on G␣ subunits is associated to the overall synaptic plasticity in neuronal cells. Finally, APT1 and its orthologue LYPLAL1 have been reported to control potassium channel dynamics based on an overexpression strategy (6).…”
Section: Discussionmentioning
confidence: 99%
“…The processes implicated in establishment of infection and parasite development are tightly controlled, and reversible posttranslational modifications such as phosphorylation play a central role in cell signaling. Palmitoylation is another posttranslational modification that has received considerable attention in recent years as it notably promotes membrane association of a vast array of soluble proteins in many eukaryotic species (1-4) while also being important for function of integral membrane proteins (5,6). Palmitoylation is an important mode of control for the accurate targeting and steady state localization of many proteins to subcellular compartments as well as for regulation of protein-protein interactions and intracellular signaling (4,5,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation